#### Answer

$n^{8/9}$

#### Work Step by Step

$\dfrac{1}{n^{-(8/9)}}=\dfrac{1}{\frac{1}{n^{8/9}}}=n^{8/9}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$n^{8/9}$

$\dfrac{1}{n^{-(8/9)}}=\dfrac{1}{\frac{1}{n^{8/9}}}=n^{8/9}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.